Different methods to define utility functions yield similar results but engage different neural processes - Heldmann, Marcus; Vogt, Bodo; Heinze, Hans-Jochen; Münte, Thomas F. (Frontiers in Behavioral Neuroscience, 2009)
Although the concept of utility is fundamental to many economic theories, up to now a generally accepted method determining a subject’s utility function is not available. We investigated two methods that are used in economic sciences for describing utility functions by using response-locked event-related potentials in order to assess their neural underpinnings. For defining the certainty equivalent (CE), we used a lottery game with probabilities to win p=0.5, for identifying the subjects’ utility functions directly a standard bisection task was applied. Although the lottery tasks’ payoffs were only hypothetical, a pronounced negativity was observed resembling the error related negativity (ERN) previously described in action monitoring research, but this occurred only for choices far away from the indifference point between money and lottery. By contrast, the bisection task failed to evoke an ERN irrespective of the responses’ correctness. Based on these findings we are reasoning that only decisions made in the lottery task achieved a level of subjective relevance that activates cognitive-emotional monitoring. In terms of economic sciences, our findings support the view that the bisection method is unaffected by any kind of probability valuation or other parameters related to risk and in combination with the lottery task can, therefore, be used to differentiate between payoff and probability valuation.